The Role of Zakat in Improving Economic Resilience Generation - Yerna Wiza; Eli Febriani (GIC Proceeding, 2025)
Zakat, as one of the pillars of Islam, plays a strategic role in improving economic resilience, especially among mustahik communities. In the digital era, the integration of financial technology (fintech) into zakat management strengthens the impact of productive zakat programs by enhancing transparency, accessibility, and efficiency. This study analyzes the synergy between zakat institutions and fintech platforms in empowering mustahik, supported by the example of digital zakat programs such as Zmart and ZISWAF crowdfunding platforms. The findings indicate that digital zakat has the potential to transform beneficiaries into muzaki, support MSME growth, and improve socio-economic inclusion